2015
DOI: 10.1111/adb.12253
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nicotine and non-nicotine smoking factors on working memory and associated brain function

Abstract: Background Smoking abstinence impairs executive function, which may promote continued smoking behavior and relapse. The differential influence of nicotine and non-nicotine (i.e. sensory, motor) smoking factors and related neural substrates is not known. Methods In a fully factorial, within-subjects design, 33 smokers underwent fMRI scanning following 24-h of wearing a nicotine or placebo patch while smoking very low nicotine content (VLNC) cigarettes or remaining abstinent from smoking. During scanning, bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 43 publications
0
25
1
Order By: Relevance
“…Eleven of nineteen (58%) studies were rated Good or Excellent quality (Supplementary Table 2 provides details on study quality). Seventeen studies included smokers who were abstinent for ≥2 h and two studies (AhnAllen et al, 2015; McClernon et al, 2016) included smokers who were abruptly switched from NNC to VLNC cigarettes for ≥2 h. Ten performance domains were identified across studies: reaction time, short-term memory, sustained attention, inhibitory control, long-term memory, response variability, motor control/functioning, visuospatial processing, learning, and verbal fluency. Most studies measured multiple domains.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eleven of nineteen (58%) studies were rated Good or Excellent quality (Supplementary Table 2 provides details on study quality). Seventeen studies included smokers who were abstinent for ≥2 h and two studies (AhnAllen et al, 2015; McClernon et al, 2016) included smokers who were abruptly switched from NNC to VLNC cigarettes for ≥2 h. Ten performance domains were identified across studies: reaction time, short-term memory, sustained attention, inhibitory control, long-term memory, response variability, motor control/functioning, visuospatial processing, learning, and verbal fluency. Most studies measured multiple domains.…”
Section: Resultsmentioning
confidence: 99%
“…Of the nineteen studies, 79% (15/19) reported that performance was significantly worse among those who smoked a VLNC versus NNC cigarette (Rose et al, 2004; AhnAllen et al, 2015; McClernon et al, 2016; Bates et al, 1995; Colrain et al, 1992; Gilbert et al, 1997; Hale et al, 1999; Harrell and Juliano, 2012; Juliano et al, 2011; Kelemen, 2008; Lee et al, 2011; Marzilli et al, 2006; Peters and McGee, 1982; Warburton et al, 1992; Marzilli and Hutcherson, 2002). This effect was observed across 7 of 10 (70%) of the performance domains, including reaction time (73% or 8/11 studies), short-term memory (30% or 3/10), sustained attention (66% or 4/6 studies), inhibitory control (25% or 1/4 studies), long-term memory (100% or 3/3 studies), and response variability (100% or 2/2 studies).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with literature indicating that the ability of tobacco products to improve executive functioning is driven by nicotine, as compared to placebo. 18,23,42,43 This literature would suggest that the smokeless tobacco product that causes the greatest influence on executive function does so as the result of its nicotine content alone. However, it is also known that factors other than nicotine can influence the response to a product [44][45][46] and not all studies of nicotine have found evidence for nicotine alone influencing executive function.…”
Section: Discussionmentioning
confidence: 99%
“…Structural MRI studies have shown that cigarette smoking leads to morphological changes (reflected as changes in fractional anisotropy [FA] and grey and white matter [WM] volume loss) in various brain structures, like the insular cortex, the right cerebellum, the parahippocampus, multiple prefrontal cortex (PFC) regions and the thalamus to name a few [12,13]. Functional MRI (fMRI) studies have revealed that chronic smoking alters the brain activity in regions involved in attention, working memory processes, higher order cognitive processing, anxiety and reward processing [14][15][16][17][18][19]. Proton magnetic resonance spectroscopy (MRS) studies on smoking have demonstrated metabolic alterations in N-acetyl aspartate (neuronal marker) and glutamate (excitatory neurotransmitter) levels in brain regions associated with reward circuitry, namely, the anterior cingulate cortex, the dorsolateral PFC, the thalamus, and the hippocampus [20][21][22].…”
Section: Introductionmentioning
confidence: 99%